EATING BEHAVIOR, BODY IMAGE, OBESITY RELATION WITH MENOPAUSAL SYMPTOMS AND LIFE QUALITY - Fidan, Ecem; Gezer, Ceren (Dokuz Eylul Univ Inst Health Sciences, 2025)
Purpose: This study aimed to examine the relationship between eating behavior, body image, and obesity with menopausal symptoms and quality of life in postmenopausal women. Methods: A total of 384 postmenopausal women participated in the study. Data was collected through face-to-face questionnaires, including the Menopause Rating Scale (MRS), Menopause-Specific Quality of Life Scale, Eating Attitudes Test, and Body Perception Scale (BPS). Anthropometric measurements such as body weight, height, waist, and hip circumferences were taken according to standard techniques. Results: Increased body mass index was associated with more severe menopausal symptoms and lower physical and sexual quality of life (p<0.05). Higher body satisfaction correlated with fewer menopausal complaints and improved overall quality of life (p<0.05). One unit increase in BPS score is associated with a 2.2% decrease in the MRS score (p<0.001). Conclusion: Postmenopausal women with a higher tendency toward obesity experience lower body satisfaction, more pronounced menopausal symptoms, and a reduced quality of life. Further multicenter studies with larger sample sizes are recommended to strengthen the evidence.
Keywords: Menopause; Quality of Life; Eating Behavior; Body Image